Parental adjustment to a burn-injured child: how to support their needs in the aftermath of the injury - Cioga, Elisabete; Cruz, Dulce; Laranjeira, Carlos (Frontiers in Psychology, 2024)
The physical pain of a burn is immeasurable, but the pain of seeing a child suffer is indescribable. Childhood burns not only affect the child directly, but also have a significant impact on the parents and the rest of the family. During the acute phase of the burn, the child’s main allies in recovery are their parents, so they face emotional turbulence, having to support their children while witnessing the painful procedures they go through. They often feel helpless and distressed because they are unable to protect their children from suffering and have difficulty managing everything they feel. In addition to the often-present feeling of guilt, they also experience sadness and worry, particularly when returning home. After hospital discharge, fears increase, as do the challenges. There is a need to readapt the entire family dynamic to respond to the needs of the burned child who returns home. This readaptation often generates stress and anxiety, interfering with the entire family structure. It is crucial to try to understand these parents and give them all the support they need. Only capable and well-adjusted parents can ensure resilient family environments with safer and calmer children, thus promoting family well-being. In this perspective paper, the authors underline the role of parents of burnt children during the long trajectory of child rehabilitation and recovery. By acknowledging their needs, feelings and challenges healthcare providers can engage and support suffering parents toward more family-centered approach.